The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/374694
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Association between Oral Hygiene and Preterm Birth by Quantitative Light-Induced Fluorescence

Abstract: The aim of this study was to investigate the purported link between oral hygiene and preterm birth by using image analysis tools to quantify dental plaque biofilm. Volunteers (n = 91) attending an antenatal clinic were identified as those considered to be “at high risk” of preterm delivery (i.e., a previous history of idiopathic preterm delivery, case group) or those who were not considered to be at risk (control group). The women had images of their anterior teeth captured using quantitative light-induced flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Systematic reviews of the literature in humans suggested an association between PD and premature low birth weight (PTLBW), miscarriage and pre-eclampsia [ 18 ], [ 19 ]. Hope et al [ 20 ] recently reported an association between plaque coverage and women who were considered to be at risk of pre-term birth. The results indicated that early localized periodontitis of the patient during pregnancy can be regarded as an important risk factor for premature birth.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews of the literature in humans suggested an association between PD and premature low birth weight (PTLBW), miscarriage and pre-eclampsia [ 18 ], [ 19 ]. Hope et al [ 20 ] recently reported an association between plaque coverage and women who were considered to be at risk of pre-term birth. The results indicated that early localized periodontitis of the patient during pregnancy can be regarded as an important risk factor for premature birth.…”
Section: Introductionmentioning
confidence: 99%
“…An expert operator could outline both regions manually using a graphical interface [ 14 , 15 ]. Also possible were semiautomatic approaches, whereby the image-processing algorithm required intervention from the dental expert to work [ 16 , 17 ], or images could be segmented automatically using image-processing techniques [ 18 - 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative light-induced fluorescence-digital (QLF-D)applied visualisation can be used to detect dental plaque on both human and animal teeth [1][2][3][4][5][6][7]. Red autofluorescence of dental plaque reflects endogenous porphyrins associated with products of microbiota metabolism [8,9]; the fluorescence of porphyrins corresponds to characteristic bands of absorbance between wavelengths of 390 nm and 425 nm, named Soret bands [10,11].…”
Section: Introductionmentioning
confidence: 99%